Inquietus sum Sulle tracce luterane della decostruzione heideggeriana del soggetto - Surace, Valentina (Bollettino Filosofico, 2020)
Heidegger’s ontology of life, which was developed during the courses of the Twenties about Paul, Augustine and Aristotle, is influenced by Lutheran methodology and anthropology. Luther’s destructio of Scholastic theology (theologia gloriae), which discovers the Invisible through the visible, is the antecedent of Heidegger’s deconstruction of classical ontology (ontologia gloriae), which immobilizes life. Their aims are to experience an incarnate and mortal God (theologia crucis) and to understand concrete life, which is inhabited by death (ontologia crucis). Luther deconstructs the old man, who is “the image and glory of God” (homo gloriens) and is oblivious to his finished condition (homo crucis) and Heidegger dismantles the metaphysical concepts of man as a rational living being (animal rationale) and the being on which everything is founded (subjectum). Heidegger leaves the naturalistic, substantive and egological conception of human life and shows that it is historical and at the world and its own character is the potentiality of being. Keywords: Deconstruction, Facticity, Heidegger, Luther, Ontology